Diagnostic leaf to evaluate the nutritional status of Jatropha - KURIHARA, CARLOS HISSAO; SILVA, CESAR JOSÉ DA (Revista Ceres, 2015)
The analytical determination of nutrient levels in recently mature leaves in order to diagnose nutritional status is based on the fact that leaves are metabolically active and more sensitive to variation in nutrients of the soil. In most of cases, there is a well known relation between foliar content and the development and yield of the plant. However, for a more accurate interpretation, it is essential to establish the index leaf. There are few published studies about Jatropha with contrasting results. In order to establish the index leaf, in adult plants, the macronutrient levels were evaluated in samples collected in experimental plots, in which doses of nitrogen and phosphorus were applied, in two parts of the floral branches (in the top and in the middle thirds); and in three positions of leaves of the floral branch (between the 1st and 3rd, 6th and 8th, and 13th and 15th leaves below the inflorescence). The location of the leaf on the plant significantly affects nutrient contents. Nitrogen, phosphorus, potassium and sulfur tend to have higher concentration in young tissues. Calcium and magnesium showed higher levels in the basal leaves of floral branches. Samples collected in the top third of plants (between the 6th and 15th leaves of the floral branch) are more sensitive to variations of nitrogen and phosphorus fertilization. Therefore, we inchcate the 6th to 15th leaves of the top third of plants as index leaves to estimate nutritional status of Jatropha.